Some Studies of Multi-Polar Fuzzy Ideals in LA-Semigroups: Some Studies of Multi-Polar Fuzzy Ideals in LA-Semigroups - Fareeha Pervaiz; Muhammad Shabir; Muhammad Aslam (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
This article’s main goal is to investigate the concept of multi-polar fuzzy sets (MPF-sets) in LA-semi-groups, which is an extension of bi-polar fuzzy sets (BPF-sets) in LA-semigroups. The main objective of this research is to extend certain significant BPF-set results to MPF-sets results. This article introduces the concepts of multi-polar fuzzy sub LA-semigroups, multi-polar fuzzy quasi-ideals, multi-polar fuzzy bi-ideals, multi-polar fuzzy generalized bi-ideals, and multi-polar fuzzy interior ideals in LA-semigroups. This article also discusses a number of fundamental aspects of multi-polar fuzzy ideals, and we use these aspects to define regular LA-semigroups.